We're told that
[tex]P(A)=\dfrac1{200}=0.005\implies P(A^C)=0.995[/tex]
[tex]P(B\mid A)=0.7[/tex]
[tex]P(B\mid A^C)=0.05[/tex]
a. We want to find [tex]P(A\mid B)[/tex]. By definition of conditional probability,
[tex]P(A\mid B)=\dfrac{P(A\cap B)}{P(B)}[/tex]
By the law of total probability,
[tex]P(B)=P(B\cap A)+P(B\cap A^C)=P(B\mid A)P(A)+P(B\mid A^C)P(A^C)[/tex]
Then
[tex]P(A\mid B)=\dfrac{P(B\mid A)P(A)}{P(B\mid A)P(A)+P(B\mid A^C)P(A^C)}\approx0.0657[/tex]
(the first equality is Bayes' theorem)
b. We want to find [tex]P(A^C\mid B^C)[/tex].
[tex]P(A^C\mid B^C)=\dfrac{P(A^C\cap B^C)}{P(B^C)}=\dfrac{P(B^C\mid A^C)P(A^C)}{1-P(B)}\approx0.9984[/tex]
since [tex]P(B^C\mid A^C)=1-P(B\mid A^C)[/tex].